A COMPARATIVE STUDY OF HEDGING AND BOOSTING DEVICES IN WRITTEN ACADEMIC DISCOURSE - Raxmonova Gulmira Baxrom qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract Hedging and boosting strategies are very essential part of written academic discourse to express writer’s politeness, uncerainty or persuasion. The research argues that hedging and boosting devices are employed frequently for different purposes like expressing caution, epistemic uncertainty or presenting arguments with greater certainty and authority. This study investigates the use of hedging and boosting devices in academic discourse in order to identify their linguistic features, pragmatic functions, and frequency of usage.